2004
DOI: 10.1007/s00436-003-1040-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the component community structure of haemoparasites in common voles ( Microtus arvalis ) from the Mazury Lake District region of Poland

Abstract: The prevalence and abundance of infections with haemoparasites were studied over a 4-year period in Microtus arvalis (common vole, n =321) sampled from fallow grassland sites in north-eastern Poland. Total species richness was five (prevalence= Haemobartonella sp. 63.9%, Bartonella spp. 27.7%, Babesia microti 9.0%, Trypanosoma sp. 8.4% and and Hepatozoon lavieri 3.1%) with 76.9% of the voles carrying at least one species and a mean infracommunity species richness of 1.1. Variation in species richness was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 30 publications
14
64
0
1
Order By: Relevance
“…In Mi. agrestis, a former study showed a prevalence of B. microti infection (9 %) comparable to our findings for this rodent species (14.3%) [Pawelczyk et al 2004]. Mi.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Mi. agrestis, a former study showed a prevalence of B. microti infection (9 %) comparable to our findings for this rodent species (14.3%) [Pawelczyk et al 2004]. Mi.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of B. microti in small mammals from Slovenia, Great Britain, Poland and Germany ranged between 1.6% and 42% [Duh et al 2003, Bown et al 2008, Karbowiak 2004, Pawelczyk et al 2004, Silaghi et al 2012. Our findings are in line with the lower range of these previous observations (2.1%).…”
Section: Discussionsupporting
confidence: 89%
“…During the last three decades, numerous surveys have been conducted in a variety of rodent communities at many locations. These surveys demonstrated that bartonellae are widely distributed in rodents of numerous species in all continents (Birtles et al,1994;Kosoy et al, 1997;Heller et al, 1998;Hofmeister et al, 1998;Laakkonen et al, 1998;Bermond et al, 2000;Fichet-Calvet et al, 2000;Bajer et al, 2001;Bown et al, 2002;Holmberg et al, 2003;Engbaek & Lawson, 2004;Gundi et al, 2004;Pawelczyk et al, 2004;Pretorius et al, 2004;Tea et al, 2004;Jardine et al, 2005;Kim et al, 2005;Telfer et al, 2005;Markov et al, 2006;Knap et al, 2007). The very first investigation of bartonella infection in rodents from tropic areas was conducted in Yunnan, a province located in southwestern China (Ying et al, 2002).…”
Section: Bartonella Infections In Rodents In Tropicsmentioning
confidence: 99%
“…They can also play an important role as reservoir hosts for vector-borne diseases such as babesiosis, borreliosis or bartonellosis. In recent years, issues concerning the role of small mammals as the aetiological factor of parasitic zoonosis have been discussed widely (Dubinský et al, 1995;Eckert & Deplazes, 2004;Deplazes et al, 2004;Pawelczyk et al, 2004;Antolová et al, 2005;Welc-Falęciak et al, 2008). The growth of interest in epizootiological studies on micromammals has contributed to the development of methods used in diagnosis of zoonotical agents within this group of hosts.…”
Section: ……mentioning
confidence: 99%